E-COMMERCE BASED SALES APPLICATION TO INCREASE PROFIT DURING COVID19 IN FURNITURE STORES - Miftahul - Jannah (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2022)
Since December 2019 there has been an outbreak that can kill thousands of people in a matter of days, while the outbreak has become a threat to a new pandemic known as Covid-19. The impact of the Covid-19 outbreak has greatly affected various sectors, one of which is the trade sector. Since the outbreak of the Covid-19 outbreak and the Government's recommendations regarding Social Distancing and the establishment of very strict health protocols, some people are reluctant to do activities outside the home so that people are more restricting themselves by staying at home. This certainly makes trade experience a slump so that it has an impact on an unstable economy and finances. the development of technology and the internet in Indonesia, has had a major impact on changes in business and sales systems. E-commerce is an internet service that is used for buying and selling online. The purpose of this research is to build an E-Commerce-based system that can help some furniture businesses in increasing sales profit, by providing convenience in the payment process. The stages of the research method that the researcher planned were to conduct survey techniques and followed by interview activities